Conservative Composite Resin Restoration for Proximal Caries – Two Case Reports - Yu OY; Zaeneldin AM; Hamama HHH; Mei ML; Patel N; Chu CH (Dove Medical Press, 2020)
Ollie Yiru Yu,1 Ahmed Mohamed Zaeneldin,1 Hamdi Hosni Hamda Hamama,2 May Lei Mei,3 Neil Patel,4 Chun-Hung Chu1 1Faculty of Dentistry, The University of Hong Kong, Hong Kong SAR, People’s Republic of China; 2Faculty of Dentistry, Mansoura University, Mansoura, Dakahlia, Egypt; 3Faculty of Dentistry, University of Otago, Dunedin, Otago, New Zealand; 4Division of Dentistry, University of Manchester, Manchester, UKCorrespondence: Chun-Hung ChuThe University of Hong Kong, 3B26, Prince Philip Dental Hospital, 34 Hospital Road, Hong Kong SAR, People’s Republic of ChinaTel +852 2859 0287Fax +852 2559 4194Email chchu@hku.hkAbstract: The paradigms of contemporary caries management have shifted to minimal intervention dentistry. Conservative restorative procedures are recommended to replace the complete removal of all carious tissues in the management of dental caries. This article reports two clinical cases of conservative restorations of proximal caries. Different conservative cavity designs and restorative techniques were performed in the two cases. Proximal caries in posterior teeth were prepared using the box-only preparation technique or the proximal tunnel preparation technique. The cavities were restored directly with resin composites. The advantages of using the box-only preparation with fissure sealant included the maximum conservation of tooth hard tissues and the prevention of unnecessary tissue removal in the occlusal surface. The tunnel preparation preserved the marginal ridge and protected the restored tooth from fracture. The filling of composites into the tunnel demonstrated a better marginal adaptation than other restorative materials. These two techniques allowed for the preservation of more healthy dental hard tissue compared with traditional techniques. Potential problems in the restoration included the high incidence of the inappropriate removal of dental hard tissue, damage of the vital pulp and the microleakage due to the polymerization shrinkage. The solutions to minimize the risk of these problems in the operative procedures were discussed.Keywords: case report, caries, restoration, resin composite, minimally invasive dentistry